Mediation of Mucosal Immunoglobulins in Buccal Cavity of Teleost in Antibacterial Immunity - Xu, Hao-Yue; Dong, Fen; Zhai, Xue; Meng, Kai-Feng; Han, Guang-Kun; Cheng, Gao-Feng; Wu, Zheng-Ben; Li, Nan; Xu, Zhen (Frontiers in Immunology, 2020)
The buccal mucosa (BM) of vertebrates is a critical mucosal barrier constantly exposed to rich and diverse pathogens from air, water, and food. While mammals are known to contain a mucosal associated lymphoid tissue (MALT) in the buccal cavity which induces B-cells and immunoglobulins (Igs) responses against bacterial pathogens, however, very little is known about the evolutionary roles of buccal MALT in immune defense. Here we developed a bath infection model that rainbow trout experimentally exposed to Flavobacterium columnare (F. columnare), which is well known as a mucosal pathogen. Using this model, we provided the first evidence for the process of bacterial invasion in the fish BM. Moreover, strong pathogen-specific IgT responses and accumulation of IgT+ B-cells were induced in the buccal mucus and BM of infected trout with F. columnare. In contrast, specific IgM responses were for the most part detected in the fish serum. More specifically, we showed that the local proliferation of IgT+ B-cells and production of pathogen-specific IgT within the BM upon bacterial infection. Overall, our findings represent the first demonstration that IgT is the main Ig isotype specialized for buccal immune responses against bacterial infection in a non-tetrapod species.